An Integrated Algorithm for Designing Oligodeoxynucleotides for Gene Synthesis - Fang, Gang; Liang, Hanjie (Frontiers in Genetics, 2022)
Design and construction of large synthetic genes can be a slow, difficult and confusing process, especially in the key step of oligodeoxynucleotides design. Herein we present an integrated algorithm to design oligonucleotide sets for gene synthesis by both ligase chain reaction (LCR) and polymerase chain reaction (PCR). It offers much flexibility with no constraints on gene to be synthesized. Firstly, it divides the long input DNA sequence by a greedy algorithm based on the length of oligodeoxynucleotides overlap region. Secondly, it tunes the length of overlap region iteratively in attempt to minimize the melting temperatures variance of overlap. Thirdly, dynamic programming algorithm is used to achieve uniform melting temperatures of oligodeoxynucleotide overlaps. Finally, the oligodeoxynucleotides with homologous melting temperature necessary for LCR-based or two-step assembly PCR-based synthesis of the desired gene are outputted.